Survivor Perspectives of Preventing Child Sexual Abuse: A Multi-level Approach - Winters, Georgia M. (Victims & offenders, 2024)
Given the significant consequences of child sexual abuse (CSA), researchers and policymakers have made considerable efforts to develop and implement prevention strategies. However, these efforts are rarely informed by those who arguably have the most expertise on the matter – survivors of CSA. The present study examined recommendations for the prevention of CSA – from the child, parent, and community level – from a sample of 52 adults who experienced CSA. Overall, the results showed that prevention is a multi-level endeavor that should target children, parents and caregivers, and the community at large.